2002
DOI: 10.1073/pnas.062055699
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of PKR and IRF-1 during hepatitis C virus RNA replication

Abstract: The virus-host interactions that influence hepatitis C virus (HCV) replication are largely unknown but are thought to involve those that disrupt components of the innate intracellular antiviral response. Here we examined cellular antiviral pathways that are triggered during HCV RNA replication. We report that (i) RNA replication of HCV subgenomic replicons stimulated doublestranded RNA (dsRNA) signaling pathways within cultured human hepatoma cells, and (ii) viral RNA replication efficiency corresponded with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
145
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(150 citation statements)
references
References 35 publications
5
145
0
Order By: Relevance
“…NS5A represses activation of PKR [121; 122; 123] through binding to PKR and inhibiting formulation of the PKR dimer [122]. NS5A also blocks the PKR-dependent activation of IRF-1 [123]. In addition, NS5A interacts with 2′-5′ OAS [124] and induces interleukin (IL) 8 [125], a chemokine that inhibits IFN activity in vivo and in vitro [126; 127].…”
Section: Subversion Of Innate Immunitymentioning
confidence: 99%
“…NS5A represses activation of PKR [121; 122; 123] through binding to PKR and inhibiting formulation of the PKR dimer [122]. NS5A also blocks the PKR-dependent activation of IRF-1 [123]. In addition, NS5A interacts with 2′-5′ OAS [124] and induces interleukin (IL) 8 [125], a chemokine that inhibits IFN activity in vivo and in vitro [126; 127].…”
Section: Subversion Of Innate Immunitymentioning
confidence: 99%
“…15 The NS5A protein binds to the catalytic site of PKR, blocking its ability to phosphorylate eukaryotic initiation factor 2 alpha and thereby inhibiting dsRNA-induced shutdown of host cell protein translation. 16 A number of important questions remain concerning the clinical importance of these in vitro observations, particularly as related to the disruption of IRF-3 signaling by the NS3/4A protease. For example, is it possible that genotype-specific differences in the ability of NS3/4A to cleave IPS-1 or TRIF might explain different rates of long-term viral persistence or different rates of response to IFN-α-based therapies?…”
Section: Hcv Interactions With Ifn Hcv (Dr Stanley Lemon Universitymentioning
confidence: 99%
“…As shown in Expression of HCV structural proteins decreases IRF-1 expression. It has been reported that in cells harboring the subgenomic replicon the double-stranded RNA-stimulated IRF-1 is specifically inhibited by NS5A expression (57). In order to distinguish between the effects of nonstructural and structural proteins, we first expressed the structural proteins of HCV in a tetracycline-regulated system (52).…”
Section: Regulation Of Irf-1 Expression In Cells Carrying Full-lengthmentioning
confidence: 99%